EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND PROMOTION TOWARDS COMPANY BRANDING - Arifani Putri Syafitri; Widiartanto Widiartanto (Universitas Diponegoro, 2017)
Modern era has induced people to dynamicly change their mindset. Change of mindset results in growth of a number of industries. One of which is Fast Moving Consumer Goods (FMCG) which gradually climb to a betterment. The growth points to the likelihood that FMCG has a relatively more competitive market, therefore every company is responsive to any changes. In order to enhance branding of company, promotion and Corporate Social Responsibility (CSR) could be one effective way.The aim of this research is to identify effect of CSR (implemented in building an eco-school of Tunas Mulia) and promotion by Wings Company towards students in Bantar Gebang as the beneficiaries. Purposive sampling method is employed to run an array of data consisting 97 respondents who are parents of Eco school of Tunas Mulia. Using quantitative data, this research was conducted with SPSS version 16. Anaysis method used were comprised of correlation test, determination, simple linier regression, multiple linier regression, T test, and F test.The result showed that there is a positive and significant correlation between CSR and promotion towards company branding of Wing Company—partially and simultaneously. Promotion variable has greater effect on branding than CSR. Corporate Social Responsibility positive and significant impact on the image of the company with the strength of the relationship is strong enough or being. However there are still some things that need to be improved include road facilities, ability to raise the spirit of learning and student achievement, awareness of personal and environmental hygiene, communication between the company and the community. Promotion of positive and significant impact on the image of the company with the strength of the relationship is strong enough or being. But there are some things that need to fix that as well as the company's public relations and public understanding of the product. The results of responden assessment of the variables corporate image is good. But there are some things that must be considered is knowledge of the company logo. Simultaneously there is a positive influence between Corporate Social Responsibility and the promotion of the image of the company in PT.Wings the strength of the relationship between all the variables are moderate.